PHILOSOPHY OF RELIGION AND MEDICINE OF PRELATE LUKE (V.F.VOYNO-YASYNETSKYI) - Васильєва, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article studies Prelate Luke’s philosophy of religion and medicine in the context of philosophical and anthropological and philosophical and cultural discourses. Particular attention is drawn to the influence of Christian culture, national spiritual tradition on the spiritual formation of personality of V.F. Voyno-Yasenetskyi, his philosophical and theological approaches.